Determinants of first-line antiretroviral treatment failure among adult patients on treatment in Mettu Karl Specialized Hospital, South West Ethiopia; a case control study - Sabit Zenu (Public Library of Science (PLoS), 2021)
Background Antiretroviral therapy has dramatically reduced Human Immunodeficiency Virus related morbidity and mortality. It has also transformed HIV infection into a manageable chronic condition. However, first-line antiretroviral treatment failure continues to grow especially in resource limited settings. Despite this, determinants of first-line antiretroviral treatment failure are not well studied in Ethiopia. Objective To identify determinants of first-line antiretroviral treatment failure among adult patients on antiretroviral therapy in Mettu Karl Specialized Hospital, South West Ethiopia, in 2020. Methods A hospital based case-control study was conducted from October to November 2020. Simple random sampling technique was used to select participants. Interviewer administered questionnaire and record review were used for data collection. Data were entered into epi data version 3.1 and exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regression analysis were used. At the end, variables with P-value < 0.05 at 95% confidence intervals for adjusted odds ratio were considered statistically significant determinants of first line treatment failure. Result A total of 113 cases and 339 controls were included in the study with response rate of 98.6%. Sixty-four (56.6%) of cases and 183 (54.0%) of controls were females. Baseline WHO clinical stage III and IV (AOR = 1.909, 95% CI: (1.103, 3.305), baseline body mass index<18.5kg/m2(AOR = 2.208,95% CI:(1.257,3.877),baseline CD4 cell count <100cells/mm3 (AOR = 3.016, 95% CI: (1.734, 5.246), having history of TB co-infection (AOR = 1.855, 95% CI: (1.027, 3.353), having history of lost to follow up (AOR = 3.235, 95% CI: (1.096, 9.551), poor adherence to medication (AOR = 7.597, 95% CI: (4.059, 14.219) and initiation of treatment after two years of diagnosis with HIV (AOR = 4.979, 95% CI: (2.039, 12.158) were determinants of first-line antiretroviral treatment failure. Conclusion In this study several variables were found to be determinants of first-line antiretroviral treatment failure. Concerned bodies should give more attention to early diagnosis of HIV, early enrollment in chronic HIV care and early initiation of ART before patients develop advanced WHO clinical stages. In addition, focus has to be given for patients with low CD4 count. Regular screening for TB, counseling on optimal adherence to medication and enhancing nutritional status of patients with low body mass index are also crucial to prevent first-line antiretroviral treatment failure.